Additive and subtractive manufacturing : emergent technologies - Davim, J. Paulo (De Gruyter series in advanced mechanical engineering ;, 2019)
Additive manufacturing (AM) and subtractive manufacturing (SM) offer numerous advantages in the production of single and multiple components. They provide incomparable design independence and are used to fabricate products in several industries, e.g.: aeronautic, automotive, biomedical, etc. The book presents recent results of processes including 3D printing, SLS (selective laser sintering), EBM (electron beam melting) and Precise Cutting and Drilling.- Resumé vydavatel